Democracy, media and law in Malaysia and Singapore a space for speech (Media, culture, and social change in Asia series, 2016)
"This book explores these issues with reference to Malaysia and Singapore. It analyses how journalists monitor governments and cover elections, discussing what difference journalism makes; it examines citizen journalism, and the constraints on it, often self-imposed constraints; and it assesses how governments control the media, including outlining the development and current application of legal restrictions".